Optimasi Usahatani Lahan Kering dengann Evaluasi Lahan di Kecamatan Playen Kabupaten Gunung Kidul - Umi Hidayati; Harsono Harsono; Tri Purwadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2003)
The objectives of this research were to evaluate land suitability for farming of corn, soybean, and groundnut in Playen District, Gunung Kidul Regency and to know the optimum suitable farming for corn, soybean, and groundnut in that area. This research was carried out during the planting season of 1999/2000. Land unit map was made by overlapping the maps of soil classification, climate, slope, land use, and administration. Matching was done between land qualities and land characteristics with land requirements for planting corn, soybean, and groundnut. After getting land suitability map, the further step was optimation by using linier program to get the optimum land suitability map for research area. The result of the research was 21 land units from 34 land units that can be calculated, while 13 other land units cannot be calculated because they had no agricultural land or land suitability class N2. Land suitability class for corn, soybean, and groundnut were S2, S3, and N2 for each commodity. The result of oprimation by using linier program made profit of Rp 6.196.992.577 in one year with three planting seasons and with planted area for the first planting season was 2.733,041 ha, and the third planting season was 2.843,841 ha. The suitable crop for the research area were 3 land units suitable for corn, 12 land units for soybean, and 6 land units for groundnut